2011
DOI: 10.1002/pbc.23215
|View full text |Cite
|
Sign up to set email alerts
|

Successful pulmonary artery embolectomy in a patient with a saddle Wilms tumor embolus

Abstract: Denys-Drash syndrome is a genetic disorder characterized by ambiguous genitalia, cryptorchidism, nephrotic syndrome, and a high predilection for Wilms tumor with intravascular invasion. We report a 5-year-old male with Denys-Drash syndrome who rapidly developed Wilms tumor with vascular invasion, subsequent saddle tumor embolus, and required emergent embolectomy. This case illustrates the rapid emergence of Wilms tumor in a patient with Denys-Drash syndrome and the importance of considering embolectomy over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Our study suggests that young and high-risk WT patients who receive intensive treatment regimens (i.e., for bilateral WT) seem to require unplanned PICU admission more often. This finding has not been described previously and is not consistently reflected in the previously reported cases of WT patients with complications requiring PICU admission [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In the SIOP93-01 and SIOP2001 studies, patients aged 6 months to 2 years were shown to have an excellent survival, with a higher event-free survival when compared to older age groups [ 2 , 3 , 32 ].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our study suggests that young and high-risk WT patients who receive intensive treatment regimens (i.e., for bilateral WT) seem to require unplanned PICU admission more often. This finding has not been described previously and is not consistently reflected in the previously reported cases of WT patients with complications requiring PICU admission [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In the SIOP93-01 and SIOP2001 studies, patients aged 6 months to 2 years were shown to have an excellent survival, with a higher event-free survival when compared to older age groups [ 2 , 3 , 32 ].…”
Section: Discussioncontrasting
confidence: 70%
“…Case reports confirm that children with WT may require unplanned intensive care treatment due to various tumor- and treatment-related emergencies. These cases revealed not only relatively well-known emergencies associated with WT at presentation, such as malignant hypertension and extensive (intracardial) tumor thrombus, but also postoperative hemorrhage, cardiomyopathy and hepatotoxicity, intracranial bleeding, and seizures [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Note that 43 documented papers (Table S1) reported paediatric patients with Wilms tumour and intravascular extension, with age in the range of 7 weeks‐16 years. Sample size ranged from 1 to 165 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 1 patient was found to have massive tumor embolism, which, to our knowledge, has only been reported in case reports. 3,[8][9][10] In a recent study from Pelland-Marcotte et al, 11 researchers compared 49 pediatric patients with MPE and SMPE combined versus patients with low-risk PE at 2 centers in Canada over a similar time period. Compared with this study, our cohort appeared to have lower proportions of infants ,1 year, cardiac disease, and presence of central venous catheters.…”
Section: Discussionmentioning
confidence: 99%